The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.03.30.486370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamical Matryoshka model: 2. Modeling of local lipid dynamics at the sub-nanosecond timescale in phospholipid membranes

Abstract: Biological membranes are generally formed by lipids and proteins. Often, the membrane properties are studied through model membranes formed by phospholipids only. They are molecules composed by a hydrophilic head group and hydrophobic tails, which can present a panoply of various motions, including small localized movements of a few atoms up to the diffusion of the whole lipid or collective motions of many of them. In the past, efforts were made to measure these motions experimentally by incoherent neutron sca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
21
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(31 citation statements)
references
References 54 publications
(67 reference statements)
10
21
0
Order By: Relevance
“…The dynamics' parameters of the slow motions of DMPC MLB135 were found to be larger for Regarding the comparison between DMPC MLB135 and DMPC MLV on IN6, it is found that while the τ1 values are similar within the errors, the D1 value and the jump distance are larger for MLVs at 283 K and 311 K. This could be due to the fact that the MLVs are generally more hydrated than MLBs [13]. The present results are also consistent with the results of the EISF/QISF analysis using the Matryoshka model, where the radius of a circle within which the whole lipid molecule can diffuse is larger for MLVs than MLBs [22].…”
Section: Slow Motionssupporting
confidence: 89%
See 4 more Smart Citations
“…The dynamics' parameters of the slow motions of DMPC MLB135 were found to be larger for Regarding the comparison between DMPC MLB135 and DMPC MLV on IN6, it is found that while the τ1 values are similar within the errors, the D1 value and the jump distance are larger for MLVs at 283 K and 311 K. This could be due to the fact that the MLVs are generally more hydrated than MLBs [13]. The present results are also consistent with the results of the EISF/QISF analysis using the Matryoshka model, where the radius of a circle within which the whole lipid molecule can diffuse is larger for MLVs than MLBs [22].…”
Section: Slow Motionssupporting
confidence: 89%
“…in the MLB or in the MLV). The τ3 values of d54DMPC MLB135 are larger than those of DMPC MLB135, indicating that the rotational jump diffusion is enhanced for the tail group compared with for the head group, which is consistent with the basic assumption of the Matryoshka model that the tail motions are faster than the head group motions[21,22]. The τ3 values of DMPC MLB45 are found to be larger than those of DMPC MLB135, implying that the fast motions show anisotropy (i.e.…”
supporting
confidence: 74%
See 3 more Smart Citations